Elderly Knowledge About Tooth Loss With Flipchart Media (Study at the Posyandu Lansia, Bringin Village, Sambikerep District, Surabaya City) - Salsabillah, Devina Sasqia; Prasetyowati, Silvia; Putri, I Gusti Ayu Kusuma Astuti Ngurah (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Introducing: Tooth loss is a common health problem in the elderly that can affect their quality of life. Based on the results of an initial survey at the Posyandu Lansia in Bringin Village, Sambikerep District, Surabaya City, as many as 14 out of 20 elderly people (70%) have less than 20 teeth that are still functioning. Problem statement: So the problem in this study is the high percentage of tooth loss in the elderly at the Elderly Posyandu in Bringin Village, Sambikerep District, Surabaya City using flipchart media. Objective: This study aims to find out the knowledge of the elderly about tooth loss with flipchart media at the Posyandu Lansia, Bringin Village, Sambikerep District, Surabaya City. Method: The research method used descriptive research with 86 elderly respondents. Data were collected through questionnaires and analyzed by calcucating percentage results, then presented in tabular form. The results: showed that the average knowledge of the elderly at the Posyandu Lansia of Bringin Village, Sambikerep District, Surabaya City, related to meaning, causes, impact and treatment of tooth loss with flipchart media is included in the category of lacking.